A new revision of Capirona (Rubiaceae, Ixoroideae, Condamineeae), with a new combination and additional notes on typification of the names involved - Delprete, Piero G. (Phytotaxa, 2020)
A new taxonomic revision of Capirona (Rubiaceae, Condamineeae) is presented. Delprete (1999) treated Condaminea macrophylla as a new synonym of Capirona decorticans; as the former name has priority over the latter, the new combination Capirona macrophylla is here proposed. Full synonymy, type citations, further notes on lectotypification of C. decorticans, and an amplified description of the single species recognized in the genus are provided. Additional type specimens (i.e., not mentioned in previous revisions) and barcodes or accession numbers for all type specimens are here cited for the first time. A preliminary conservation assessment is proposed using the IUCN Red List Categories and Criteria.